Definition, prevalence and predictive factors of benign multiple sclerosis - Tatjana Reynders; Miguel D'haeseleer; Jacques De Keyser; Guy Nagels; Marie B. D'hooghe (eNeurologicalSci, 2017)
Background: Multiple sclerosis (MS) is characterized by a great inter-individual variability in disease course and severity. Some patients experience a rather mild course, controversially called ‘benign MS’ (BMS). The usefulness of this entity in clinical practice remains unclear. Methods: We performed a literature search in PubMed, Web of Science and Cochrane Library databases from November 1980 to December 2015, using the following key words: benign multiple sclerosis, diagnosis, imaging, prognosis, predictive, natural history and predefined inclusion criteria. Results: Our search yielded 26 publications. Most definitions were based on the Expanded Disease Status Scale (EDSS), which is heavily weighted towards physical disability. Between 30 and 80% of relapsing-remitting MS patients have EDSS <3 or 4 at 10 years after onset. Having only one relapse in the first 5 years and EDSS ≤2 at 5 years or EDSS ≤3 at 10 years appears to be predictive for a prolonged benign disease course, without protecting against disease progression at a later stage. Evidence on the predictive value of MRI parameters remains limited. Conclusions: Current BMS definitions have some predictive value for future physical disability, but do not take into account the age at EDSS and the potentially disrupting effects of non-EDSS symptoms and cognitive impairment. It appears to correspond to mild RRMS in the first decades and its prevalence varies. Since early and accurate prediction of BMS is not yet possible, the clinical relevance is limited. Research approaches are suggested.